Effect of Cutting Age on the Resistance of Prunus cerasifera (Myrobalan Plum) to Meloidogyne arenaria - Esmenjaud, D (Journal of nematology, 1995)
The response of softwood cuttings of Myrobalan plum infested after 50 and 105 days with 3,000 second-stage juveniles (J2) of Meloidogyne arenaria was compared to 15-month-old hardwood cuttings in 13 genotypes ranging from highly resistant to susceptible. Gall index and number of galls were recorded 30 days after infestation. Fifty-day-old cuttings rooted in perlite developed many rootlets, but had only incipient galls after infestation. In sand, rooting of 50-day-old cuttings not treated with indolebutyric acid (IBA) hormone was so variable that their resistance could not be assessed. Similar cuttings rooted with IBA developed more galls, but neither number of galls per plant nor gall index was a reliable criterion for determination of host suitability. Because of the better rooting results with IBA treatment, 105-day-old cuttings were first rooted with IBA in perlite and then transferred into sand for nematode inoculation. Known highly resistant genotypes of Myrobalan plum were gall-free and the responses of other genotypes paralleled that of the reference hardwood cuttings, although the test was less discriminating. Expression of M. arenaria host suitability in Myrobalan plum depends on root tissue maturation and cannot be reliably evaluated with 50-day-old cuttings